Synthesis, electrochemical and spectroelectrochemical properties of phthalocyanines having extended pi-electrons conjugation - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The synthesis of novel, symmetrical zinc and manganese phthalocyanines bearing eight ethynylthiophene moieties was achieved by cyclotetramerization of 4,5-bis(thiophen-3-ylethynyl)phthalonitrile with suitable metal salts. 4,5-Bis(thiophen-3-ylethynyl)phthalonitrile was obtained through Sonogashira-coupling reaction. The new compounds have been characterized by using elemental analyses, UV-vis, IR, H-1 NMR and mass spectroscopic data. Electrochemical and spectroelectrochemical studies show that MnPc gives two metal-based reduction processes in addition to the one ring-based reduction and one ring-based oxidation process. However ZnPc gives only ring based electron transfer reactions. Due to the ethynylthiophene groups substituted on the periphery of ZnPc, the spectral changes during the first reduction process are completely different than the MPcs in the literature. Ethynylthiophene groups substituted on the periphery of the complexes provide electropolymerization of the complexes during the anodic potential scans. Types of the metal center of the complexes affect the character of the polymerization processes. All redox processes of the complexes shift to the positive potentials when compared with the similar complexes in the literature due to extending IT electron conjugation of Pc ring with ethynylthiophene groups. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; Electropolymerization; Ethynylthiophene; Phthalocyanine; Spectroelectrochemistry; Sonogashira-coupling; SITU ELECTROCOLORIMETRIC CHARACTERIZATION; UNSYMMETRICAL PHTHALOCYANINES; MANGANESE PHTHALOCYANINES; METALLOPHTHALOCYANINES